Improved cuckoo search for loss allocation in transmission line/ Nur Atiqah Abdul Rahman - Abdul Rahman, Nur Atiqah; Abdul Rahman, Titik Khawa (Universiti Teknologi Mara Cawangan Pulau Pinang, 2017)
Electricity market reformation often involes the process of liberalisation, deregulation and privatisation. Privatisation has often resulted in competition between market participants in order to reduce cost and increase efficiency. Researchers have gained interest to allocate the transmission loss in transmission line which will lead to fair allocation of cost among market participants. Thus this paper proposed a new technique called Improved Cuckoo Search (ICS) as an approach to allocate transmission loss in transmission line. This technique is an improvement from previous technique called Cuckoo Search (CS), where cauchy distribution based on mutation technique is used instead of Levy Flight for its searching operator. The technique has been tested with IEEE 30 bus system in normal condition and showed improvement in terms of computational time and accuracy. Comparison between Cuckoo Search (CS) and Genetic Algorithm (GA) are also presented in this paper.